2016
DOI: 10.1039/c6gc01447j
|View full text |Cite
|
Sign up to set email alerts
|

Autohydrolysis pretreatment of softwood – enhancement by phenolic additives and the effects of other compounds

Abstract: The effects of different additives on lignin repolymerisation in the autohydrolysis pretreatment of softwood and the consequences for enzymatic cellulose digestibility have been studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 15 publications
0
43
0
Order By: Relevance
“…The selected studies use spruce or pine as feedstock, which were shown to have a very similar behavior of recalcitrance and can equally profit from the addition of 2-naphthol to pretreatment [40]. The studies employ a solid content in enzymatic hydrolysis of 2–3% w/w, which is in good agreement with the solid content in the hydrolysis of the 2-naphthol experiments (2.2–3.0% w/w) and allows for a good comparability.…”
Section: Resultsmentioning
confidence: 99%
“…The selected studies use spruce or pine as feedstock, which were shown to have a very similar behavior of recalcitrance and can equally profit from the addition of 2-naphthol to pretreatment [40]. The studies employ a solid content in enzymatic hydrolysis of 2–3% w/w, which is in good agreement with the solid content in the hydrolysis of the 2-naphthol experiments (2.2–3.0% w/w) and allows for a good comparability.…”
Section: Resultsmentioning
confidence: 99%
“…Pretreatment conditions not only affect saccharification yields 12 but also suitability of the lignin for value-added applications. Lignins isolated around the optimal intensified pretreatment conditions were therefore analysed for their chemical properties.…”
Section: Lignin Characterisationmentioning
confidence: 99%
“…Lignocellulose is recalcitrant and requires a pretreatment step in order to release the majority of sugar contained within. 7 Various pretreatment methods are currently under development, such as steam explosion, 8 AFEX, 9 concentrated acid, 10 dilute acid, 11 hot water, 12 organosolv 13,14 and ionic liquid pretreatments, [15][16][17] including ionoSolv fractionation. 18,19 Different strategies are followed, from disrupting the lignocellulosic cell wall structure without separation, [20][21][22][23] to selectively isolating lignin, hemicelluloses and cellulose.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these reactions take place at the aliphatic chain and beneficially block the lignin condensation reactions. Obvious examples are alkoxylation Kubo, Kadla 2004;Lancefield et al 2017) and sulphonation (Lou et al 2013;Zhou et al 2013b) at the C-α position, and reactions with so-called carbocation scavengers supplemented to autohydrolysis pretreatments Pielhop et al 2016;. Acidic hydrothermal processes form resinous degradation products, termed pseudo-lignin or humins, which resemble lignin in terms of structural features Van Zandvoort et al 2013) and in their detrimental adsorption of cellulases ).…”
Section: Structural Changes In Lignin During Common Lignocellulose Prmentioning
confidence: 99%